MAPPING THE LECTURER PERFORMANCE LANDSCAPE: BIBLIOMETRIC ANALYSIS OF LITERATURE 2015-2024 - Pratidina, Ginung (Jurnal Governansi, 2026)
The objective of this study is to map the research landscape of lecturer performance for the 2015-2024 period. The research method uses a bibliometric approach to 199 Scopus documents with the keyword "Performance Lecturer". Descriptive analysis of annual and country trends and co-occurrence mapping using VOSviewer (network, density, and overlay) was conducted. The results show an increasing trend in publications, with a spike in 2020 of 32 documents and in 2024 of 35 papers published in Scopus. The geographic distribution shows Indonesia's dominance as the largest contributor, followed by Malaysia and other countries; therefore, this topic appears to be accelerating in Southeast Asia. Thematic mapping displays two main interconnected clusters. First, the managerial-organizational cluster includes leadership, motivation, organizational culture, commitment, path analysis, and private universities. Second, the pedagogical-technological cluster encompasses students, learning, teaching, systems, processes, evaluation/assessment, technology, implementation, and the pandemic, with connecting methodological terms such as variable, respondent, role, time, and software/data collection. These findings imply the need for integrated lecturer performance indicators that balance organizational and pedagogical dimensions, standardised measurement for cross-study comparability, expanded cross-country collaboration to reduce regional bias, and the use of learning technology to encourage measurable lecturer performance improvements at the individual and institutional levels. The mapping results provide an empirical basis for higher education leaders and policymakers to design interventions and further research agendas on lecturer performance.